1999
DOI: 10.1080/00016489950180621
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Electrical Stimulation of the Auditory Nerve using Non-charge-balanced Stimuli

Abstract: This study was designed to evaluate the pathophysiological response of the cochlea following long-term intracochlear electrical stimulation using a poorly charge-balanced stimulus regime, leading to direct current (DC) levels >0.1 microA. Four normal-hearing adult cats were bilaterally implanted with scala tympani electrode arrays and unilaterally stimulated for periods up to 2200 h. Stimuli consisted of 50 micros monophasic current pulses presented at 2000 pulses per second (pps) per channel, and resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…The DC is highly dependent on time, stimulation amplitude, and stimulation frequency but not significantly on the distance between the electrodes. These levels of DC would most certainly lead to tissue damage as they are typically one or two orders of magnitude higher than the 2-3 lA level for which damage has already been seen [10,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DC is highly dependent on time, stimulation amplitude, and stimulation frequency but not significantly on the distance between the electrodes. These levels of DC would most certainly lead to tissue damage as they are typically one or two orders of magnitude higher than the 2-3 lA level for which damage has already been seen [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that DC levels as low as 2-3 lA cause pathological changes in rat spinal cords [10] or in cat auditory nerves [18]. Therefore, both the U.S. Food and Drug Administration (FDA) and E.U.…”
Section: Introductionmentioning
confidence: 99%
“…Charge balanced stimulation pulses are important for patient safety and preventing electrode degeneration. DC current flows of 100 nA across an electrode have been correlated with tissue damage in animal models [8] and industry targets a DC error of < 25 nA [26]. The stimulator proposed here is capable of stimulating at over 1500 pulses per second, but will in practice only be used to deliver up to 80 stimulations per second per channel (based on maximum observed firing rates of human proprioceptors [37], [38]).…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In practice safe stimulation means that the packet of charge delivered to the tissue also needs to be removed -giving a charge balanced stimulation. Unbalanced stimulations give rise to DC currents flowing across the electrode / tissue interface and have been linked with tissue damage and deterioration of the electrode [8].…”
Section: Introductionmentioning
confidence: 99%
“…One of the original numbers (below 100 nA DC current error) was cited for a cochlear implant study [12] and has been cross-cited numerous times also for other applications [5]. This number has also been used by the European cochlear implant standard [13].…”
Section: Introductionmentioning
confidence: 99%